STIMULASI PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA 4-6 TAHUN DI TK NEGERI PEMBINA BAUBAU - Andina Kabakoran; Rachman Saleh; Marwah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the process of stimulating social-emotional development in children aged 4–6 years through five educational games at TK Negeri Pembina Baubau, as well as to measure children's social-emotional developmental achievements across five key indicators following the structured implementation of those games. The study employed a Participatory Action Research (PAR) approach, conducted collaboratively between the researcher and the classroom teacher through four cyclical stages: planning, action, observation, and reflection. The research subjects consisted of 21 children from Group A aged 4–6 years. Data were collected through observation, interviews, and documentation, with data validity ensured through source and technique triangulation. The findings reveal that the implementation of five educational games, marble maze, snakes and ladders, colorful balls, block stacking, and animal puzzle, facilitated actively and reflectively by the teacher, proved effective in stimulating children's social-emotional development. Children's achievements across all indicators showed significant improvement, shifting from the category of Not Yet Developed to Developing as Expected and Developing Very Well. These findings contribute to the attainment of SDGs Goal 4 on Quality Education through the strengthening of inclusive and meaningful early childhood developmental stimulation.